Les adhésifs à photopolymérisation radicalaire employés pour le collage structural du verre en conservation-restauration - Sandra Gillioz (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper evaluated the suitability in terms of mechanical resistance of UV adhesives for the bonding of glass in conservation. Four UV adhesives– Conloc® 665 (EGO®), Loctite® 350 (Henkel®), NOA® 61 (Norland Optical Adhesives®) and Verifix® LV740 (Bohle®) – were compared with the reference epoxyde in the field - Hxtal® Nyl-1 (Hxtal Adhesive®).